Does an increase in visits to general practice indicate a malignancy?. Issue 1 (December 2016) - Hauswaldt, Johannes; Hummers-Pradier, Eva; Himmel, Wolfgang
Abstract Background An increase in a patient's visits to doctors usually raises concerns and may be a 'red flag' for a patient's deterioration of health. The aim of this study was to analyze whether an increase of patient-physician contacts is a first sign of a malignancy in a patient's near future. Methods This is a retrospective case-control study. From 153 German general practices' electronic patient records (EPR), cases with at least one new malignancy diagnosis and no-malignancy controls were matched for gender and age. We calculated (1) the number of contacts in the first quarter up to the sixth quarter before a malignancy diagnosis was made and (2) the inter-contact interval (ICI), i.e. the time lag between two consecutive patient-physician contacts measured in days. Differences between cases and controls were investigated in several analyses of variance, with group and time as main factors. Results A total of 3, 310 cases and 3, 310 controls could be included. The number of contacts for cases in the six quarters before a malignancy diagnosis increased from 4.8 contacts (SD 4.3) to 5.5 contacts (SD 4.8). The number of contacts for controls increased only marginally from 4.3 contacts (SD 3.6) to 4.5 (SD 4.2). The factor 'group' (cases vs. controls) was highly significant in the analyses of variance, also 'time' and the interaction 'group * time'. The effect size, however, was very small (R2 being less than 0.02), which is the equivalent for about one additional contact per quarter in cases directly before a newly made malignancy diagnosis. Conclusion An increase in contact frequency is a call for GPs to become more attentive towards these patients. It may raise the suspicion of an impending serious disease but the increase is not so dramatic and unique that it can be interpreted a reliable sign of a malignant diagnosis.